Poverty Reduction during 1971-2013 Periods:Success and its Recent Trends in Bangladesh (Global Journal of Human-Social Science, 2014)
This paper analyses data on poverty for 1971-2013 periods and finds that, Bangladesh reduces national poverty by 55.82 percent during these periods. Moreover, nearly 44 percent people are found extremely poor who earn less than $1.25 per day and 77 percent people are moderately poor who earn less than $2 per day. Though, absolute income poverty declines but income inequality rises by 30 percent in these periods. However, different international indexes disclose that, Bangladesh also reduces human poverty. Bangladesh is no longer the member of 'alarmingly hunger countries' and will become the member of 'Medium human development countries' by 2014. Besides, about 58 percent people are found multi-dimensionally poor, who suffer from overlapping deprivations in health, education and standard of living. Finally, this paper makes a comparison between Bangladesh and other south Asian countries and finds that, Bangladesh has the highest level of poverty followed by India in this region.
Keywords: poverty; income inequality; human development; population; bangladesh; south asia